High Temperatures and Tourism: Findings from China - Yu D; Li S; Chen NC; Hall M; Guo Z (MDPI (Basel, Switzerland), 2023)
Climate change and its fluctuations exert significant impacts on the tourism industry, particularly through the influence of high temperatures as typical meteorological and climatic factors on tourists’ travel intentions, spatial behavior preferences, and destination choices. This study employs China as a case study to investigate the effects of high-temperature weather on tourism and tourist travel. By analyzing news reports, conducting observations, and examining statistics, an exploratory analysis of tourism in China under high-temperature scenarios reveals several noteworthy findings. Firstly, tourists seeking relief from the summer heat exhibit a preference for short-distance trips and destinations rich in natural resources. Secondly, heat-escape tourism products have gradually transformed over time, evolving from mountain heat escapes in the 1980s to waterfront vacations in the 1990s, artificial water leisure in the 2000s, and ultimately culminating in the development of heat-escape cities in the 2010s. Additionally, this study examines interregional disparities in summer tourism climate amenity across China using the Holiday Climate Index (HCI), the Tourism Climate Index (TCI), and daily data from 775 weather stations. It also provides a summary of the spatiotemporal evolution from 1961 to 2020 within the context of climate change, revealing intriguing findings. Moreover, a case study of Shanghai Disneyland demonstrates the greater significance of the holiday system compared to temperature constraints. This study aims to examine the interaction between high temperatures and China’s tourism in the context of climate change, providing a scientific foundation for government agencies and tourism enterprises to develop effective policies and plans.
Keywords: heat-escape tourism; climate change; climate amenity; Holiday Climate Index (HCI); Tourism Climate Index (TCI); Shanghai Disneyland